Multiband antenna for GSM and 3G Mobile System - M. M. Owag, Abdurahman (2006)
We propose a new design for built-in handset antennas in that metal strips as additional resonators are directly connected with a feed strip. With the new design scheme, a multi-band antenna for covering GSM900 and UMTS2000 bands for use in mobile built-in handsets are experimentally carried out. Compared with the parasitic form with a shorted strip placed away from the main radiator, the size of the proposed antennas can be reduced by an order of 10 20%, which is desirable since the size of mobile phones is becoming smaller according to consumer preferences. Moreover, the impedance matching for each band of the new antennas becomes easy. The new multi-band handset antenna is developed within the limits of a 36 *16* 8 mm3 volume. The antenna is also analyzed using the finite-difference time-domain technique